Handbook of lithium and natural calcium chloride : their deposits, processing, uses and properties - Garrett, Donald E. (Elsevier Academic Press, 2004)
This book is concerned with two major industrial minerals: Lithium and Calcium Chloride. The geology of their deposits is first reviewed, along with discussions of most of the major deposits and theories of their origin. The commercial mining and processing plants are next described, followed by a review of the rather extensive literature on other proposed processing methods. The more important uses for lithium and calcium chloride are next covered, along with their environmental considerations. This is followed by a brief review of the production statistics for each industry, and some of their compounds' phase data and physical properties. - Describes the chemistry, chemical engineering, geology and mineral processing aspects of lithium and calcium chloride - Collects in one source the most important information concerning these two industrial minerals - Presents new concepts and more comprehensive theories on their origin.